Bioimmobilized Limestone Powder for Autonomous Healing of Cementitious Systems: A Feasibility Study - Nafeesa Shaheen; Rao Arsalan Khushnood; Siraj Ud din (Advances in Materials Science and Engineering)
For preserving concrete structures and hindering ingress of chemicals through cracks and fissures, repair is inevitable. Microbial calcite precipitation is an intrinsic approach for crack rectification and emulating way of sustainability for reducing anthropogenic greenhouse gases (GHGs) along with conserving the natural resources. In this study, Bacillus subtilis strain is applied for intrinsic repair of concrete’s cracks because of its high pH endurance and capability of sporulation. For prolonged survival of microorganisms, immobilization technique was employed. B. subtilis was immobilized through limestone powder (LSP) before adding into cement matrix. Self-healing proficiency of B. subtilis was deliberated in terms of mechanical strength regain after cracking at 3, 7, 14, and 28 days. To examine the microstructure and characterization of healing precipitate, micrographical (field emission scanning electron microscopy), chemical (energy dispersive X-ray), and thermal (thermogravimetric analysis) analyses were performed after the healing period of 28 days. The results revealed evident signs of calcite precipitation in nano-/microcracks subsequent to microbial activity. Furthermore, immobilized LSP improved the compressive strength of the analyzed formulations.